Linguistic and Literary Creativity in Philippine Englishes - Martin, Isabel Pefianco (Archīum Ateneo, 2024)
Creativity in Englishes in the Philippines is evident in both literary and non-literary works produced in current contexts of multilingualism. The term ‘creativity’ is traditionally associated with language use in literary texts, suggesting that a systematic study of creativity in language use lies only in the esoteric fields of literary studies and creative writing. However, I wish to approach ‘creativity’ in the sense of what Carter describes as ‘not simply a property of exceptional people but an exceptional property of all people’. I approach creativity in Englishes in the Philippines as ‘everyday creativity’, beginning with a discussion of Braj Kachru's concept of ‘bilinguals’ creativity’, introduced in a 1985 groundbreaking work. This Kachruvian concept of creativity is revisited in the light of 21st century sociolinguistic realities. In this revisiting, I extend the concept of bilinguals’ creativity beyond traditional approaches to creativity in English language use.